Peran Tujuan Pembelajaran dalam Perencanaan Pembelajaran : Dasar untuk Pembelajaran yang Efektif - Meyniar Albina; Krisna Bayu Pratama (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
An effective learning plan requires a strong foundation to achieve optimal learning outcomes. One of the main elements of this plan is the learning objectives. Learning objectives are formulated with clear and measurable characteristics and become the main guideline for educators to determine the steps to be taken in carrying out learning activities. The purpose of this research is to determine the role of learning objectives in basic learning planning for effective learning. This research method uses a qualitative approach with literature study, by collecting and analyzing several relevant articles and books. From this research the author found three discussion results, firstly learning objectives as a basis for the learning process, secondly the relationship between learning objectives and learning planning, thirdly the application of learning objectives in effective learning. Therefore, learning objectives not only provide direction for teaching and learning activities, but also function as a tool for creating meaningful and effective learning experiences.